A child with Fetal Alcohol Syndrome (FAS) - nursing care - Anna Rozensztrauch; Natalia Świątoniowska; Kinga Tomaszewska; Aleksandra Kołtuniuk (Kazimierz Wielki University, 2018)
Fetal Alcohol Syndrome (FAS) is the group of conditions observed in children who happened to be exposed to the effects of alcohol in their prenatal development. Some very characteristic symptoms, belonging to three groups, such as: craniofacial abnormalities, physical development deficiency and the central nervous system damage, can be distinguished in people with FAS. It also significantly affects the person's behaviour. The main objective of the research is to present the problems that a girl suffering from a fetal alcohol syndrome has to struggle with. The work has been prepared on the basis of the available literature analysis as well as of the nursing process. A method of an individual case study has been applied. The nursing care of a child with FAS should definitely involve routine caring activities, however with particular attention paid to their psychological aspect. The child suffering from FAS must be treated in a very individual way, basically due to his/her cognitive disorder. A nurse should strictly follow 8 precisely fixed principles.